(untitled) (Texas Journal of Medical Science, 2023)
Type 2 diabetes mellitus belongs to the risk factors for the development of cardiovascular diseases, which are currently the main cause of early disability and mortality in the workingage population. According to Panzram G., diabetes mellitus increases mortality 2-3 times, the risk of coronary heart disease and myocardial infarction - 2 times, kidney pathology - 17 times, gangrene of the lower extremities - 20 times, arterial hypertension - more than three times.